The Effect of Gymnema Sylvestre on Motivation to Consume Sweet Foods—A Qualitative Investigation - Nelson I; Kruger R; Hsiao D; Stice E; Ali A (MDPI (Basel, Switzerland), 2025)
Background/Objectives: Excessive intake of sugar-sweetened food (SSF) increases obesity risk. Various psychological, physiological, and environmental factors may drive high consumption of SSF. Due to blocking sweet tastes, the herb Gymnema sylvestre (GS) has been shown to reduce SSF consumption, but its impact on motivation to eat SSF is unknown. This research aimed to qualitatively investigate adults’ perceptions regarding effects of GS on their motivation to eat SSF when administered systematically (three times/day in-between meals, i.e., GS-SYS treatment) or ad libitum (up to six times/day at participants’ discretion, i.e., GS-ADLIB) over 14 days, compared to placebo (taste-matched mint; PLAC-SYS). Methods: This study represents the qualitative investigation of a placebo-controlled randomised cross-over trial, conducted as three 14-day phases. The qualitative investigation included interviews at baseline and three post-testing phases. Seven participants (mean age 34.7 ± 13.8 years; two males, five females) agreed to participate. Twenty-eight interviews (across phases) were thematically analysed using NVivo software, identifying themes and highlighting changes in motivation to eat SSFs across the study. Results: The GS-SYS and GS-ADLIB treatments made SSFs unpleasant to eat and increased mindful eating, subsequently increasing motivation to avoid SSFs. External factors could increase or decrease motivation, depending on individual circumstances. Participants preferred GS-SYS and GS-ADLIB over PLAC-SYS, feeling it was more effective at changing behaviours related to SSF intake. Self-control over SSF intake changed during the study, mostly due to external factors, and in part GS-ADLIB. Conclusions: Participants found both GS administrations successful as motivation to avoid SSF; GS-ADLIB was considered most effective.
Keywords: Gurmar; impulse; sugar-sweetened; behaviour; mindful eating; pleasant